THE IMPACT OF SOCIO- DEMOGRAPHIC VARIABLES ON CUSTOMER SATISFACTION WHEN USING DIGITAL SERVICES OF HOTELS - Zakić, Nebojša; Ćirić, Maja; Ćurčić, Nikola (Ekonomija - teorija i praksa, 2022)
The development of information and communication technologies is fundamentally transforming the tourism sector and tourism suppliers are widely using modern technologies to improve their business. Hotels are increasingly relying on digital technologies in an effort to reach their business objectives, improve the experience and satisfaction of their guests and achieve a competitive advantage. The aim of this research is to determine the statistical significance of the impact of demographic variables on customer satisfaction when using digital services, such as: the hotel website, online reservations, internet services, as well as social media. Empirical research on customers’ attitudes and their satisfaction with digital services that 4- and 5- star-hotels provide on the territory of Serbia was conducted in 2021 and the results were processed using statistical methods and the Chi-square test. The research results have shown that there is a statistically significant difference in customer satisfaction with digital hotel services depending on their gender and age. The research indicates that it is necessary to take in account the demographic categories of customers when developing digital hotel services and make adjustments to them accordingly.